For a short time, we were the best version of ourselves: Hurricane Harvey and the ideal of community. Issue 1 (23rd August 2019) - Baker, Natalie D.; Deham, Magdalena
Abstract : Purpose: The authors use a co-auto-ethnographic study of Hurricane Harvey where both authors were citizen responders and disaster researchers. In practice, large-scale disaster helps temporarily foster an ideal of community which is then appropriated by emergency management institutions. The advancement of disaster research must look to more radical perspectives on human response in disaster and what this means for the formation of communities and society itself. It is the collective task as those invested in the management of crises defer to the potentials of publics, rather than disdain and appropriate them. The authors present this work in the advancement of more empirically informed mitigation of societal ills that produce major causes of disaster. The authors' work presents a departure from the more traditional disaster work into a critical and theoretical realm using novel research methods. The paper aims to discuss these issues. Design/methodology/approach: This paper produces a co-auto-ethnographic study of Hurricane Harvey where both authors were citizen responders and disaster researchers. Findings: The authors provide a critical, theoretical argument that citizen-based response fosters an ephemeral utopia not usually experienced in everyday life. Disasters present the possibility of an ideal of community. These phenomena, in part, allow us to live our better selves in the case of citizen response and provide a direct contrast to the modern experience. Modernity is a mostly fabricated, if not almost eradicated sense of community. Modern institutions, serve as sources of domination built on the backs of technology, continuity of infrastructures and self-sufficiency when disasters handicap society, unpredictability breaks illusions of modernity. There arises a need to re-engage with those around us in meaningful and exciting ways. Research limitations/implications: This work produces theory rather than engage in testing theory. It is subject to all the limitations of interpretive work that focuses on meaning and critique rather than advancing associations or causality. Practical implications: The authors suggest large-scale disasters will persist to overwhelm management institutions no matter how much preparedness and planning occurs. The authors also offer an alternative suggestion to the institutional status quo system based on the research; let the citizenry do what they already do, whereas institutions focus more on mitigate of social ills that lead to disaster. This is particularly urgent given increasing risk of events exacerbated by anthropogenic causes. Social implications: The advancement of disaster research must look to more radical perspectives on human response in disaster and what this means for the formation of communities and society itself. It is the collective task as those invested in the management of crises to defer to the potentials of publics, rather than disdain and appropriate them. The authors also suggest that meaningful mitigation of social ills that recognize and emphasize difference will be the only way to manage future large-scale events. Originality/value: The authors' work presents a departure from the more practical utility of disaster work into a critical and highly theoretical realm using novel research methods.